2007
DOI: 10.1042/bst0351219
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic memory mechanisms: Alzheimer's disease amyloid β-peptide-induced dysfunction

Abstract: There is growing evidence that mild cognitive impairment in early AD (Alzheimer's disease) may be due to synaptic dysfunction caused by the accumulation of non-fibrillar, oligomeric Abeta (amyloid beta-peptide), long before widespread synaptic loss and neurodegeneration occurs. Soluble Abeta oligomers can rapidly disrupt synaptic memory mechanisms at extremely low concentrations via stress-activated kinases and oxidative/nitrosative stress mediators. Here, we summarize experiments that investigated whether cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
6

Year Published

2009
2009
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 51 publications
5
115
0
6
Order By: Relevance
“…Interestingly although LTP was unaffected in TNF receptor-deficient mice, LTD could not be recorded in these animals (Albensi and Mattson, 2000). To our knowledge, this is the first report of a similar change in dentate gyrus in vivo; although TNF-␣ has been implicated as a factor which contributes to the inhibition of LTP induced by A␤ in vivo (Rowan et al, 2007). As previously reported, the age-related decrease in LTP was attenuated in rats treated with rosiglitazone (Loane et al, 2009) and the evidence suggested that the effect was mediated by IL-4 which is released from astrocytes .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly although LTP was unaffected in TNF receptor-deficient mice, LTD could not be recorded in these animals (Albensi and Mattson, 2000). To our knowledge, this is the first report of a similar change in dentate gyrus in vivo; although TNF-␣ has been implicated as a factor which contributes to the inhibition of LTP induced by A␤ in vivo (Rowan et al, 2007). As previously reported, the age-related decrease in LTP was attenuated in rats treated with rosiglitazone (Loane et al, 2009) and the evidence suggested that the effect was mediated by IL-4 which is released from astrocytes .…”
Section: Discussionmentioning
confidence: 78%
“…Thus predictably, IL-1␤ inhibits LTP in vitro and in vivo (Curran et al, 2003;Murray and Lynch, 1998) and H 2 O 2 has also been shown to exert a similar detrimental effect, at least at low concentrations in young animals (Kamsler and Segal, 2003;Vereker et al, 2001). An inhibitory effect of TNF-␣ on LTP has also been reported (Butler et al, 2004;Cumiskey et al, 2007;Tancredi et al, 1992) and it has been identified as a key mediator in the inhibitory effect of A␤ on LTP (Rowan et al, 2007). Recent evidence has indicated that when inflammatory and oxidative stress are inhibited by overexpression of mitochondrial transcription factor A (TFAM), the age-related decrease in LTP in CA1 is ameliorated (Hayashi et al, 2008), while eicosapentaenoic acid, which exerts anti-inflammatory and antioxidative effects similarly restores LTP in aged rats Martin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly a decade ago TNF was reported to alter synaptic transmission in hippocampal slices (Tancredi et al, 1992). Several years later (Wang et al, 2005b;Rowan et al, 2007), it was shown that this earlier observation explained the ability of A␤, through TNF, to do the same. Other researchers expanded the roles of TNF in this context (Pickering et al, 2005;Stellwagen et al, 2005).…”
Section: Tnf Causes Insulin Resistance: Implications For Admentioning
confidence: 99%
“…Given the unique anti-amyloidogenic activity of HC F1, we used this molecule to investigate the in vivo therapeutic potential of free HCs using a rodent model of A␤ oligomer impairment of hippocampal LTP, which is a measurable correlate of long term memory and learning (45)(46)(47). Fig.…”
Section: Monoclonal Hcs Inhibit Amyloid Fibril Growth and Prevent A␤-mentioning
confidence: 99%